2014
DOI: 10.1158/1078-0432.ccr-13-2943
|View full text |Cite|
|
Sign up to set email alerts
|

TP53 Mutation Spectrum in Breast Cancer Is Subtype Specific and Has Distinct Prognostic Relevance

Abstract: This study reveals that TP53 mutations have different clinical relevance in molecular subtypes of breast cancer, and suggests diverse roles for TP53 in the biology underlying breast cancer development.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
242
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 255 publications
(280 citation statements)
references
References 39 publications
32
242
3
Order By: Relevance
“…For METABRIC, we downloaded the normalized gene expression profiles generated using the Illumina HT 12 IDATS platform and the clinical information from the European genome-phenome archive (EGAS00000000083). The mutation calls for TP53 generated by Sanger sequencing of coding exons used were from the work by Silwal-Pandit et al (10). A3B del polymorphism genotypes were identified using Nexus Copy Number 7.0 software (BioDiscovery Inc.) to process Affymetrix-generated CEL files (EGAD00010000164).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For METABRIC, we downloaded the normalized gene expression profiles generated using the Illumina HT 12 IDATS platform and the clinical information from the European genome-phenome archive (EGAS00000000083). The mutation calls for TP53 generated by Sanger sequencing of coding exons used were from the work by Silwal-Pandit et al (10). A3B del polymorphism genotypes were identified using Nexus Copy Number 7.0 software (BioDiscovery Inc.) to process Affymetrix-generated CEL files (EGAD00010000164).…”
Section: Methodsmentioning
confidence: 99%
“…Analyses of cell line and tumor datasets have shown that A3B gene expression is up-regulated in malignant vs. normal tissues and epithelial cell lines and have shown correlations between A3B expression and the presence of certain somatic mutations, particularly in TP53 (7,10) and PIK3CA (phosphatidylinositol-4,5-bisphosphate 3-kinase, catalytic subunit alpha) (11). Although the factors that cause up-regulation of A3B in cancer cell lines and tumors remain unknown, these observations form the basis for a model where A3B expression contributes to the accumulation of somatic alterations during the process of carcinogenesis and subsequent evolution, and it has been suggested that inhibition of this activity could represent a strategy for cancer prevention or an adjuvant to other therapies (7,12).…”
mentioning
confidence: 99%
“…Furthermore, a wealth of in vitro data as well as data from animal models indicate that the oncogenic activities of TP53 variants are heterogeneous and can vary according to the tissue type and the genetic background of the cells (33)(34)(35)(36). In breast carcinoma, the spectrum of TP53 variants is subtype specific, each one with a different prognostic relevance (37). Classifying TP53 status as either "wild-type" or "mutant" is therefore an oversimplification, as TP53-null tumors due to loss of p53 expression have a different phenotype compared to tumors overexpressing an oncogenic TP53 variant.…”
Section: Heterogeneity Of Tp53 Variantsmentioning
confidence: 99%
“…2B; Table 1) [9]. Conversely, the frequency of TP53 mutations (29%) is higher in luminal B cancers and is associated with worse outcome [20].There is also higher frequency of ATM loss and CCND1, CDK4, CDK6, and MDM2 amplifications in luminal B cancers [9]. ER-positive cancers have relatively few recurrent CNAs compared with TNBCs (Table 1) [9,10,21,22].…”
Section: The Genomic Landscape Of Breast Cancersmentioning
confidence: 99%
“…These cancers have the highest frequency of TP53 disabling mutations (up to 80%) [9,20]. Mutations and/or deletions in RB1 (retinoblastoma 1; 20%) and mutations in PIK3CA (9%), MLL3 (5%), and GATA3 (2%), as well as amplification of the CCNE1 gene (9%), occur at relatively low frequencies (Fig.…”
Section: Triple-negative Breast Cancersmentioning
confidence: 99%